Manajemen Pengembangan Sumber Daya Manusia dalam Meningkatkan Prestasi Kerja Tenaga Kependidikan untuk Memperbaiki Pelayanan Pendidikan di MI. Ma‟arif Bego Yogyakarta - Nurlena Nurlena (GHAITSA : Islamic Education Journal, 2024)
The purpose of this study was to determine the management of human resource development, the educational achievements of existing education personnel, and educational services in madrasah. This study uses qualitative research with a naturalistic inquiry approach. The primary data in this study are the head of madrasah, teaching staff and education staff. Meanwhile, secondary data are data and archives related to this research. Data collection techniques through observation, interviews, and documentation. Data analysis techniques were performed by data reduction, data presentation, and data verification. The results showed that: First, human resource development management has not been realized because of the need for careful planning in financing, facilities and infrastructure, time, who is responsible for developing HR development programs, good coordination of the head of madrasah and existing education personnel for activities can run smoothly, and the need for supervision so that it can be seen that HR development activities have been going according to plan or not. The head of the madrasah has carried out his duties properly using a social approach to make it easy for education staff to express their opinions. In the education staff development strategy, namely selection, placement of employees, and the welfare of education personnel, it has been running and has received attention by madrasas. Second, in terms of the work performance of the teaching workforce, special attention is still needed because the assessment of the work performance of education personnel is already in madrasah, but the data has not been documented. Third, the supporting factors for human resource development management in improving work performance to improve education services, namely support from the government and foundations related to funds and implementation of HR development programs, as well as adequate facilities and infrastructure. Meanwhile, the inhibiting factor for the management of human resource development in improving the work performance of education personnel is to improve education services in MI. Ma'arif Bego, namely inadequate facilities and infrastructure, educational staff who are not suitable for their fields, and lack of motivation to move forward from education personnel. So in this case, the results of the management of human resource development that have not been maximal, have not been able to improve the work performance of teaching personnel and improve educational services in MI. Ma'arif Bego.